2017
DOI: 10.18632/oncotarget.22679
|View full text |Cite
|
Sign up to set email alerts
|

3D-structured illumination microscopy reveals clustered DNA double-strand break formation in widespread γH2AX foci after high LET heavy-ion particle radiation

Abstract: DNA double-strand breaks (DSBs) induced by ionising radiation are considered the major cause of genotoxic mutations and cell death. While DSBs are dispersed throughout chromatin after X-rays or γ-irradiation, multiple types of DNA damage including DSBs, single-strand breaks and base damage can be generated within 1–2 helical DNA turns, defined as a complex DNA lesion, after high Linear Energy Transfer (LET) particle irradiation. In addition to the formation of complex DNA lesions, recent evidence suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 43 publications
5
53
0
Order By: Relevance
“…A limitation of the present study is the lack of proof of the relationship between levels of HMGB1 release and number of DSBs in tumor cells. By quantification of clustered DSBs using a super-high-resolution microscope system, Hagiwara et al suggested that closely localized DSBs are a risk factor for the formation of chromosomal rearrangement after C-ion RT [ 26 ]. The use of such a high-resolution microscope system may facilitate understanding of HMGB1 release under high-LET radiation.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the present study is the lack of proof of the relationship between levels of HMGB1 release and number of DSBs in tumor cells. By quantification of clustered DSBs using a super-high-resolution microscope system, Hagiwara et al suggested that closely localized DSBs are a risk factor for the formation of chromosomal rearrangement after C-ion RT [ 26 ]. The use of such a high-resolution microscope system may facilitate understanding of HMGB1 release under high-LET radiation.…”
Section: Discussionmentioning
confidence: 99%
“…In cells undergoing DNA damage repair, RPA forms foci that are similar to those observed in VRCs [49,50]. To determine if the focal RPA32 was associated with DDR signaling, the hyperphosphorylated form of RPA32 (pRPA32 S4S8 ) and phosphorylated ATM kinase (pATM S1981 ) were visualized.…”
Section: Focal Rpa32 Is Associated With Ddr Signaling Proteinsmentioning
confidence: 96%
“…Experimental methods for detecting complex DNA damage have evolved in recent decades [24,[30][31][32][33][34][35][36]. Among several techniques [24,[30][31][32][33][34][35][36], microscopic operations coupled with an antibody against γ-H2AX [31][32][33][34] enables researchers to obtain spatial distributions of DSB induction in the cell nucleus. The adjacent degree of the DSB site can be evaluated from γ-H2AX foci volume in an assay [35,36]; however, the damage complexity at the nano-meter scale (the scale of DNA) cannot be obtained due to the limited spatial resolution from hundreds of nm to a few µm [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Among several techniques [24,[30][31][32][33][34][35][36], microscopic operations coupled with an antibody against γ-H2AX [31][32][33][34] enables researchers to obtain spatial distributions of DSB induction in the cell nucleus. The adjacent degree of the DSB site can be evaluated from γ-H2AX foci volume in an assay [35,36]; however, the damage complexity at the nano-meter scale (the scale of DNA) cannot be obtained due to the limited spatial resolution from hundreds of nm to a few µm [35,36]. Meanwhile, complex DNA damage composed of BD can be quantified by means of gel electrophoresis after treatment of base excision repair enzymes [24,30,37,38] and fluorescence resonance energy transfer [39,40].…”
Section: Introductionmentioning
confidence: 99%